Elements of economics of industry : - Marshall, Alfred (Macmillan and co., 1923)
This volume is an attempt to adapt the first volume of my Principles of economics to the needs of junior students: preliminary survey, some fundamental notions, on wants and their satisfactions, the agents of production land, labour, capital and organization, the balancing of demand and supply.